Application of Milkfish Skin Gelatin (Elops hawaiensis) as A Stabilizer in Panna cotta Dessert Products - Ratna Sari, Dea; Haryati, Sakinah; Hasanah, Afifah Nurazizatul (Barakuda 45: Jurnal Ilmu Perikanan dan Kelautan, 2025)
The skin of payus fish (Elops hawaiensis) is a by-product of the bontot processing industry in Pontang, Serang Regency, Banten, which has the potential to be utilized as an alternative source of halal gelatin serving as a stabilizer in panna cotta desserts. This study aimed to characterize gelatin extracted from payus fish skin and to determine the optimal concentration of payus fish skin gelatin on the characteristics of panna cotta dessert products. The method used was a Completely Randomized Design (CRD) with one treatment factor, namely the concentration of payus fish skin gelatin at 0.5%, 1%, and 1.5%, and a control using commercial bovine gelatin. Gelatin analysis included yield, proximate composition, pH, and viscosity, while panna cotta analysis included gel strength, proximate composition, and hedonic tests on appearance, aroma, taste, and texture. The results showed that payus fish skin gelatin contained 7.7% moisture, 1.04% ash, protein 74% (bk), fat 8.4%, pH 6.3, 0.15% carbohydrates, and viscosity of 3.8 cP, which met the Indonesian National Standard (SNI) 06-3735-1995. The application of payus fish skin gelatin in panna cotta at a concentration of 1% produced the best treatment, with gel strength of 639.3 g bloom, moisture content of 75.1%, ash 3.5%, protein 5.5%, fat 1.8%, and carbohydrates 14.1%. The hedonic test results for appearance (4.03), texture (3.9), aroma (4.13), and taste (3.50) indicated that the product was rated from neutral to liked by the panelists. Therefore, payus fish skin gelatin at an optimal concentration of 1% had potential as an alternative to commercial gelatin in panna cotta dessert products.